2019
DOI: 10.1111/adb.12845
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin receptor antagonism of fentanyl‐induced conditioned place preference, intravenous self‐administration, and dopamine release in the nucleus accumbens in rats

Abstract: The extended occurrence of fentanils abuse associated with the dramatic increase in opioid fatal overdoses and dependence strongly emphasizes insufficiencies in opioid addiction treatment. Recently, the growth hormone secretagogue receptor (GHS-R1A) antagonism was proposed as a promising mechanism for drug addiction therapy. However, the role of GHS-R1A and its endogenous ligand ghrelin in opioid abuse is still unclear. Therefore, the aim of our study was to clarify whether the GHS-R1A antagonist JMV2959 could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 46 publications
2
23
0
1
Order By: Relevance
“…We also showed that the systemic administration of JMV2959 was long-lasting and effective, which suggests a crucial role of the ghrelin-GHSR1A pathway in the regulation of drug addiction. Other studies have reported the inhibitory effect of JMV2959 on addictive drug reward memory in other drugs, such as methamphetamine, fentanyl, and cocaine ( Engel et al, 2015 ; Jerabek et al, 2017 ; Havlickova et al, 2018 ; Sustkova-Fiserova et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We also showed that the systemic administration of JMV2959 was long-lasting and effective, which suggests a crucial role of the ghrelin-GHSR1A pathway in the regulation of drug addiction. Other studies have reported the inhibitory effect of JMV2959 on addictive drug reward memory in other drugs, such as methamphetamine, fentanyl, and cocaine ( Engel et al, 2015 ; Jerabek et al, 2017 ; Havlickova et al, 2018 ; Sustkova-Fiserova et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…The disruption of drug memory reconsolidation has been suggested as a promising strategy to prevent relapse ( Lin et al, 2014 ). A number of studies have demonstrated that ghrelin and its specific receptor GHSR1A are involved in the mediation of memory reward-related neurological processes ( Havlickova et al, 2018 ; Sustkova-Fiserova et al, 2019 ). Thus, targeting these neuronal processes could disrupt memories underlying addiction behaviour ( Engel et al, 2015 ; Jerabek et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, systemic or central administration of ghrelin potentiates the effects of central stimulants (e.g., amphetamine and cocaine) on locomotor stimulation and CPP (Wellman et al, 2005 ; Davis et al, 2007 ; Jang et al, 2013 ; Schuette et al, 2013 ; Dunn et al, 2019 ), whereas GHSR-1A antagonists attenuate these behavioral responses in rodents (Jerlhag et al, 2010 ; Abizaid et al, 2011 ; Clifford et al, 2012 ; Suchankova et al, 2016a ; Havlickova et al, 2018 ; Wenthur et al, 2019 ; Edvardsson et al, 2021 ). Further, the acute rewarding effect of opiates and its relationship with the GHSR-1A is evident as JMV2959 inhibits the dopaminergic release in NAc and CPP caused by morphine or fentanyl (Engel et al, 2015 ; Sustkova-Fiserova et al, 2016 , 2020 ; Jerabek et al, 2017 ). Besides, JMV2959 reduces morphine-induced locomotor stimulation and stereotypic behavior in male rodents (Sustkova-Fiserova et al, 2014 ).…”
Section: Appetite-regulatory Peptides In Substance Use Disordermentioning
confidence: 99%
“…В последние годы акцент в исследовании механизмов зависимости сделан на изучении аномального функционирования эмоциогенных структур мозга, активация которых во многом зависит от центральных механизмов стресса (система структур расширенной миндалины, или параамигдалярного комплекса). Особенно неясным и противоречивым является вопрос о роли нейропептидов расширенной миндалины в регуляции подкрепляющих систем мозга [16,17].…”
unclassified